How can African agriculture adapt to climate change: Green and Blue Water Accounting in the Limpopo and Nile Basins: Implications for Food and Agricultural Policy - Sulser, Timothy B.; Ringler, Claudia; Zhu, Siwa; Bryan, Elizabeth; Rosegrant, Mark W. (International Food Policy Research Institute, 2011)
Water scaricity is an increasingly critical issue for food production around the world. This is particularly true for the world's poorest region, Sub-Saharan Africa, due to its growing malnutrition and almost complete dependence on rainfed agriculture. Given that agriculture is the primary consumer of freshwater around the globe and the demand for domestic, industrial, and environment water uses is steadily rising, strategies for the sustainable use of water in agriculture are urgently needed